2008
DOI: 10.1051/0004-6361:20078953
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRAL observations of Hercules X-1

Abstract: Aims. We investigate the X-ray spectral and timing properties of the accreting X-ray pulsar Her X-1 observed with the INTEGRAL satellite in July-August 2005. Methods. The data analyzed in this work cover a substantial part of one main-on state of the source. The short time scale pulse period development is measured. X-ray pulse profiles for different energy ranges and time intervals are constructed. Pulse-averaged and pulse-phase resolved broad band X-ray spectra are studied. Spectral changes during X-ray dips… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 40 publications
6
42
1
Order By: Relevance
“…While there is no commonly accepted interpretation of the pulse profile dependence on energy and luminosity, we note that similar behavior is observed in Her X-1 (Klochkov et al 2008b), 4U 0115+63, and V 0332+63 (Tsygankov et al 2007). A qualitative interpretation of the pulse profile energy-dependence (based on the results of Mowlavi et al 2006) has been proposed by Tsygankov et al (2007) to explain the variation in V 0332+63 pulse profiles in a purely geometric fashion: if the axis of the magnetic dipole is at an angle to the rotation axis (a necessary condition to observe pulsation), the neutron star itself can eclipse some of the lower parts of the accretion columns, which are thought to primarily emit the harder photons.…”
Section: Timing Resultssupporting
confidence: 74%
“…While there is no commonly accepted interpretation of the pulse profile dependence on energy and luminosity, we note that similar behavior is observed in Her X-1 (Klochkov et al 2008b), 4U 0115+63, and V 0332+63 (Tsygankov et al 2007). A qualitative interpretation of the pulse profile energy-dependence (based on the results of Mowlavi et al 2006) has been proposed by Tsygankov et al (2007) to explain the variation in V 0332+63 pulse profiles in a purely geometric fashion: if the axis of the magnetic dipole is at an angle to the rotation axis (a necessary condition to observe pulsation), the neutron star itself can eclipse some of the lower parts of the accretion columns, which are thought to primarily emit the harder photons.…”
Section: Timing Resultssupporting
confidence: 74%
“…1 of Staubert et al 2007) we display observed values of the pulse phase averaged centroid cyclotron line energy as a function of time, covering the complete history of observations since the discovery of the line in 1976. We combine historical data, as taken from the compilation by Gruber et al (2001, their Tables 2 and 3) for the time before the RXTE era, published values from observations with RXTE and INTEGRAL (Klochkov et al 2006;Staubert et al 2007;Klochkov et al 2008a) and with Suzaku (Enoto et al 2008), as Staubert et al (1983Staubert et al ( , 2013 well as recent values as given in Table 2 (see also Staubert 2013;Fürst et al 2013). For the analysis of the long-term variation of E cyc we exclude values with 35 d phases >0.20 in order to avoid contamination due to a possible third variable, the 35 d phase (a dependence, if any, is very weak for small phases; see Fig.…”
Section: Variation Of E Cyc With Time -Long-term Variationmentioning
confidence: 99%
“…A CRSF is clearly seen in the spectrum around 37 keV, but its energy is strongly variable with pulse phase. In International Gamma-Ray Astrophysics Laboratory (INTEGRAL) data, Klochkov et al (2008) found that it changes from around 30 keV in the off-pulse to over 40 keV during the main peak of the pulse profile. It is now also firmly established that the line energy correlates positively with the X-ray luminosity (Staubert et al 2007;Vasco et al 2011;Staubert 2013).…”
Section: Introductionmentioning
confidence: 99%